2001
DOI: 10.1302/0301-620x.83b6.0830868
|View full text |Cite
|
Sign up to set email alerts
|

Primary glenoid dysplasia

Abstract: W e reviewed 12 patients with primary glenoid dysplasia. Ten were assessed clinically and two from case notes and radiographs. We identified two groups according to the age at onset of symptoms. The first (seven patients) consisted of boys and younger men, all of whom developed symptoms before the age of 40 years. All four children were free from pain, whereas the three adults in this group had varying degrees of this. Four patients had symptoms of instability. The second group consisted of older men (five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Pain and mild disability persisted in two patients who had radiographic signs of arthritis preoperatively, and these radiographic changes progressed. We also observed that both were older than 40 years of age at the time of the procedure, and in accordance with the observations of Smith and Bunker [46], with increasing age the symptoms are generally more disabling and the results of this procedure may be less predictable. Our results suggest that the procedure may be more reliable in patients without degenerative joint changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pain and mild disability persisted in two patients who had radiographic signs of arthritis preoperatively, and these radiographic changes progressed. We also observed that both were older than 40 years of age at the time of the procedure, and in accordance with the observations of Smith and Bunker [46], with increasing age the symptoms are generally more disabling and the results of this procedure may be less predictable. Our results suggest that the procedure may be more reliable in patients without degenerative joint changes.…”
Section: Discussionsupporting
confidence: 92%
“…Nonoperative management in patients with atraumatic posterior shoulder instability associated with glenoid dysplasia may provide initial but inconsistent symptom relief [46,55], but it cannot solve its underlying causes [26]. Surgical options in these patients, who often are younger, focus on joint-preserving treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In children, scapular neck dysplasia is generally asymptomatic (Smith & Bunker, 2001). Some cases remain symptomless in adulthood, and may be discovered as incidental findings (Edwards, 1928;Kozlowski et al, 1985;Wirth et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that cases of primary glenoid dysplasia may remain symptomless has led some (e.g. Pettersson, 1981;Collins et al, 1995;Smith & Bunker, 2001;de Bellis et al, 2001) to suggest that the anomaly may not be as rare in modern populations as the number of clinically identified cases might suggest. Other than the cases cited above, I am aware of no other reports of similar deformities in the palaeopathology literature (indeed Bennike et al (1987) were likewise unable to find other reported palaeopathology cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation